Implementasi Peraturan Bupati Banyuwangi Nomor 59 Tahun 2017 Tentang Penyelenggaraan Mal Pelayanan Publik - Dimas Imaniar (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2023)
The Banyuwangi district government is currently always faced with limitations and challenges, starting with matters of budget, human resources, authority, to time. These limitations and challenges then gave birth to two solutions, namely innovation and collaboration. "Innovation and collaboration of many parties make public services better." In this study, a qualitative paradigm research method was used because the researcher wanted to be able to describe and explore the implementation of innovative program policies in Banyuwangi Regency by collecting data through interviews, observation and communication. The results of this study indicate that (1) the form of implementation of public service malls in Banyuwangi Regency. (2) the implementation of public service malls as a new paradigm to anticipate service problems in Banyuwni Regency (3) The meaning and function of implementing public service malls in Banyuwangi Regency.